New synthesis of (±)-cis-trikentrin A via tandem indole aryne cycloaddition/Negishi reaction. Applications to library development - Brown, Neil (2009)
We describe herein an efficient new route to the trikentrins and their related structures using a tandem 6,7-indolyne cycloaddition/Negishi cross-coupling reaction starting from a 4,6,7-tribromoindole (obtained in good yield via the Bartoli indole synthesis). The key step of this second generation route to the trikentrins is based on our observation that the 7-bromo substituent appears to undergo selective metal–halogen exchange and elimination to give the 6,7-indolyne, which is trapped in the presence of excess cyclopentadiene. Subsequent Negishi cross-coupling at the 4-bromoindole position with Et(2)Zn gave directly the same intermediate obtained from our previous work. Application of this chemistry to the construction of trikentrin-related libraries using this general cycloaddition/cross-coupling tactic will also be described.